Exploring Lecturers' Attitudes in Online Learning: Phenomenological Studies at Private Islamic Colleges in South Sumatra - Muhamad Faizul Amirudin; Aflatun Muchtar; Abdurrahmansyah Abdurrahmansyah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to explore the attitudes of lecturers in online learning in the environment of the South Sumatra Private Islamic Religious University. The research method used is qualitative with a phenomenological approach. The subject of this study is a lecturer who teaches at the South Sumatra Private Islamic Religious College and the chairman of the PTKIS South Sumatra Forum. Data collection techniques through interviews, observation and documentation. Data analysis uses the model formulated by Creswell, first reading the entire data, second doing coding, third applying the coding process, fourth describing the theme to be presented in the qualitative report, and fifth interpreting the data. Based on the results of the study, it was found that online learning has not been accepted as an ideal learning system because it is considered ineffective to be implemented in the environment of the South Sumatra Private Islamic Religious University. This is caused by several factors, namely, 1) inadequate digital infrastructure and financial capabilities, 2) lecturers' technological competence that has not been maximized, 3) A more emphasized factor is the desire to maintain a face-to-face system to maintain an emotional or inner connection between lecturers and students that is considered better than virtual interaction. Islamic education actually has dynamic principles that open up opportunities to adapt to the development of science and technology. Suppose it relates to curriculum, media or learning tools and methods. Then the solution is to use a blended learning model.